(untitled) (American Journal of Pedagogical and Educational Research, 2023)
A sense of emotional balance is a basis for success, creativity and innovation at work, as it is a necessity of intellectual production for any individual in society, and at any age, always to creative work, and the positive evaluation of the individual by his sense of emotional stability pushes him to others to make the person aware of himself and evaluate it is a positive way, which makes him feel a sense of reassurance and security, but in the case of a lack of a sense of balance, and the feeling of fear increases in the human psyche, and the person who loses the sense of emotional stability, will tend to be insecure in all his other life matters, problems appear, troubles and mistakes abound, and therefore he works to destroy himself.